The Meaning of Income for Employees: A Household Accounting Perspective - Argadiredja, Haurina Maknuun; Reyna Oktavia Adytira; Setu Setyawan; Masiyah Kholmi; Agung Prasetyo Nugroho Wicaksono (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2026)
Purpose: The article explores the meaning of income for employees from a household accounting perspective at one of Indonesia’s largest military defense technology companies Method: Descriptive qualitative approach using data collection techniques such as open-ended questionnaires, in-depth interviews, and observations of 12 employees.Results: Income is interpreted and managed differently across genders, showing that household financial practices are shaped not only by economic needs but also by social roles. Novelty: This study offers a household accounting perspective that reveals income as a socially constructed concept influenced by gender, extending beyond its traditional economic definition.Contribution: Strengthening theoretical knowledge and literacy regarding household accounting. Abstrak: Makna Pendapatan Bagi Karyawan: Perspektif Akuntansi Rumah TanggaTujuan: Artikel ini mengkaji makna pendapatan bagi karyawan dari perspektif akuntansi rumah tangga di salah satu perusahaan teknologi pertahanan militer terbesar di Indonesia.Metode: Pendekatan kualitatif deskriptif dengan menggunakan teknik pengumpulan data berupa kuesioner terbuka, wawancara mendalam, dan observasi terhadap 12 karyawan.Hasil: Pendapatan diinterpretasikan dan dikelola secara berbeda antar gender, menunjukkan bahwa praktik keuangan rumah tangga tidak hanya dibentuk oleh kebutuhan ekonomi tetapi juga oleh peran sosial.Keunikan: Studi ini menawarkan perspektif akuntansi rumah tangga yang mengungkap pendapatan sebagai konsep yang dibangun secara sosial dan dipengaruhi oleh gender, melampaui definisi ekonomi tradisional.Kontribusi: Penguatan pengetahuan teoretis dan literasi mengenai akuntansi rumah tangga.